Influence of CaO Content on the Fly Ash-Lime System Hydro-Thermal Synthesis Reaction Under Autoclave Curing - ZHU Chenhui; JIAO Baolong; CHEN Runbo (Nantong Daxue xuebao. Ziran kexue ban)
Based on the low temperature-synthesized fly ash cement,with the ordinary pressure curing replaced by autoclave curing,the effects of calcium oxide content on the fly ash-lime system hydro-thermal synthesis reaction is studied,especially the effect of CaO content to the cement pastes strength is investigated.The changes of phase composition,micro-structure and morphology are characterized by means of XRD and SEM analysis.The results show that with the increase of CaO content,the amount of β-C_2S and C12A_7in the gelling material also increase accordingly.While when the content of CaO is too high,the amount ofβ-C_2S and C12A_7in the gelling material fails to increase,and the strength will also be somewhat lost.